2021
DOI: 10.3390/metabo11030187
|View full text |Cite
|
Sign up to set email alerts
|

Goldfish Response to Chronic Hypoxia: Mitochondrial Respiration, Fuel Preference and Energy Metabolism

Abstract: Hypometabolism is a hallmark strategy of hypoxia tolerance. To identify potential mechanisms of metabolic suppression, we have used the goldfish to quantify the effects of chronically low oxygen (4 weeks; 10% air saturation) on mitochondrial respiration capacity and fuel preference. The responses of key enzymes from glycolysis, β-oxidation and the tricarboxylic acid (TCA) cycle, and Na+/K+-ATPase were also monitored in various tissues of this champion of hypoxia tolerance. Results show that mitochondrial respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 57 publications
4
30
0
Order By: Relevance
“…Chronic hypoxia causes a general decrease in CPT ( Table 6 ) and 3-hydroxyacyl-CoA dehydrogenase (HOAD) activity (another enzyme that regulates β-oxidation; Table 7 ). The only two exceptions to this pattern are CPT activation in tench liver and red muscle [ 62 ], and HOAD activation in goldfish brain [ 51 ]. Otherwise, general downregulation of β-oxidation appears to be a common way to adjust ATP supply to the lower energy demand afforded by hypometabolism.…”
Section: Membrane Lipids: Response To Environmental Stress and How They Affect Metabolism Ion Pumps And Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic hypoxia causes a general decrease in CPT ( Table 6 ) and 3-hydroxyacyl-CoA dehydrogenase (HOAD) activity (another enzyme that regulates β-oxidation; Table 7 ). The only two exceptions to this pattern are CPT activation in tench liver and red muscle [ 62 ], and HOAD activation in goldfish brain [ 51 ]. Otherwise, general downregulation of β-oxidation appears to be a common way to adjust ATP supply to the lower energy demand afforded by hypometabolism.…”
Section: Membrane Lipids: Response To Environmental Stress and How They Affect Metabolism Ion Pumps And Channelsmentioning
confidence: 99%
“…For instance, mitochondrial respiration for various states and tissues is lowered in frogs [ 97 ] and eastern oysters [ 98 ], but remains unchanged in killifish liver [ 99 ] and snapper heart [ 100 ]. Respiration states of goldfish mitochondria show different responses across tissues [ 51 ]. Overall, it is impossible to predict how mitochondria respond to chronic hypoxia because some animals maintain respiration capacity while many others prefer to: (i) regulate specific respiration states that impact ATP turnover, (ii) change mitochondrial efficiency, (iii) change mitochondrial abundance, or (iv) use a combination of the above.…”
Section: Membrane Lipids: Response To Environmental Stress and How They Affect Metabolism Ion Pumps And Channelsmentioning
confidence: 99%
“…Although our understanding of metabolic responses to reduced O 2 availability and related changes in metabolites is generally patchy in species adapted to hypoxia, there are several common patterns of hypoxia-induced metabolic remodelling that have emerged in champions of hypoxia-tolerance, such as goldfish, certain species of freshwater turtles, ground squirrels, and various African mole-rat species [1,[18][19][20][21]. For example, at the wholeanimal level, marked metabolic rate suppression is observed in many of these species during periods of acute or prolonged hypoxia or anoxia, which is achieved by a wide variety of organ-specific reductions in cellular and systemic function, such as decreases in excitatory neurotransmitter release, suppression of action potentials, and reduced ion permeability in brain as well as liver, etc.…”
Section: Introductionmentioning
confidence: 99%
“…As intermitochondrial junctions were not the subject of the study, this may simply be sampling bias of the images, but anoxic mitochondrial interconnectivity and junctions present an avenue for future investigation. Bundgaard et al [ 196 ] found no change in the abundance of ETC complexes one, two or five in cold or anoxic turtle heart [ 196 ]; however, Farhat et al [ 268 ] found a decrease in cytochrome c oxidase respiration in all tissues tested in anoxic goldfish, except for heart. They concluded that the decrease in complex four respiration was likely indicative of a decrease in mitochondrial abundance.…”
Section: Mitochondrial Distribution and Dynamics On The Anoxic Cytoskeletonmentioning
confidence: 99%